Planning Location of Mobility Hub for Sustainable Urban Mobility - Aydin, Nezir; Seker, Sukran; Ozkan, Betuel (ELSEVIER, 2022)
Mobility hubs facilitate access to many transportation modes, such as public transportation, bike sharing, bus rapid transit (BRT), metro or car sharing, to enable travelers become more mobilized by providing advantage of their socio-economic benefits. Mobility hubs also help to lessen greenhouse gas emissions by decreasing private vehicle usage and giving equal priority to all modes of travel, including walking, cycling and other active forms of transport, i.e. public transport, ridesharing, taxis and private motor vehicles. Thus, emerging and inspiring the usage of diverse modes of transportation with less influence on the environment is one of the main policy to decrease people's environmental footprint. Since the locations of mobility hubs play an important role to achieve this goal by attracting travelers and encouraging people to use different modes of mobility options that has less impact on environment, the location selection of such hubs requires a strategic decision for authorities and policy makers. With this motivation, in this study, an integrated fuzzy multi criteria decision-making (MCDM) methodology that consists of interval type-2 fuzzy Analytic Hierarchy Process (AHP) and interval type-2 fuzzy Weighted Aggregated Sum Product Assessment (WASPAS) is proposed to select the best location for a new mobility hub location in the Anatolian side of Istanbul. Among alternative locations Kadiko & BULL;y is found as the best location for building a mobility hub to expand shared-use mobility and public transport options at a major transit station for Istanbulers in Anatolian side. At the end of the study, Sensitivity analysis is conducted to validate results of the proposed approach.
Keywords: Mobility Hub; location selection; interval type-2 fuzzy AHP; interval type-2 fuzzy WASPAS,& nbsp; sustainable city; DECISION-MAKING; MCDM APPROACH; WASPAS METHOD; GIS; PREFERENCES; CITY; Construction & Building Technology; Science & Technology - Other Topics; Energy & Fuels